(untitled) (Journal of Asian Development Studies, 2018)
Poverty is the denial of basic human rights. It is today of concern to all societies. The main theme of the research is to highlight the factors behind this evil. The study also focuses on the role of international iststitutions. The research discusses the different socio-economic and political factors in this regard. The Approach of the research is analytical and comparative. The study also analyzes the role of international institutions to eradicate the poverty. The efforts made by big powers are also discussed. The researcher uses original and secondary sources. The references and conclusion is in the end.